ANALISIS STRATEGI BERSAING PADA MEBEL IRJAM PUTRA DI KOTA TIMIKA - Albertus Evaldo Saputra Dodu; Abu Bakar (CV. ADIBA AISHA AMIRA, 2023)
This study aims to determine the competitive strategy in Irjam Putra Furniture. The research method used is descriptive research method, namely a research method that describes or describes something, for example circumstances, conditions, situations, events, activities, and others. In this study the data collection methods used were observation methods, interview methods, questionnaire methods, and documentation methods. To find out the right competitive strategy, the analytical instrument used in this study is an analysis of the current situation, namely SWOT analysis. The results of this study indicate that the position of developing a competitive strategy lies in quadrant III (WO), which means that this business faces large market opportunities but on the other hand faces several internal constraints/weaknesses, the focus of this strategy is to minimize internal problems, so that it can seize better market opportunities